The Effect of Restriction Shape On Laminar Natural Convection Heat Transfer In A Vertical Circular Tube - Salman, Dr. Yasin K.; Mohammed, Hussein Ahmed (Al-Khwarizmi Engineering Journal, 2017)
Natural convection heat transfer is experimentally investigated for laminar air flow in a vertical circular tube by using the boundary condition of constant wall heat flux in the ranges of (RaL) from (1.1*109) to (4.7*109). The experimental set-up was designed for determining the effect of different types of restrictions placed at entry of heated tube in bottom position, on the surface temperature distribution and on the local and average heat transfer coefficients. The apparatus was made with an electrically heated cylinder of a length (900mm) and diameter (30mm). The entry restrictions were included a circular tube of same diameter as the heated cylinder but with lengths of (60cm, 120cm), sharp-edge and bell-mouth. The surface temperature along the cylinder surface for same heat flux would be higher values for circular restriction with length of (120cm) and would be smaller values for bell-mouth restriction. The results show that the local Nusselt number (Nux) and average Nusselt numberare higher for bell-mouth restriction and smaller values for (120cm) restriction. For all entry shape restrictions, the results show that the Nusselt number values increases as the heat flux increases. From the present work an empirical correlations were obtained in a form of (Log) versus (Log) for each case investigated and obtained a general correlation for all cases which reveals the effect of restriction existence on the natural convection heat transfer process in a vertical circular tube.